Bio-inspired aptamers decorated gold nanoparticles enable visualized detection of malathion - Li, Peng; Zhan, Haonan; Tao, Sijian; Xie, Zhuohao; Huang, Jiahao (Frontiers in Bioengineering and Biotechnology, 2023)
Biosensors always respond to the targets of interest in a specific manner, employing biological or bio-mimic recognition elements such as antibodies and aptamers. Inspired by target recognition in nature, an aptamer-mediated, gold nanoparticle-based sensing approach is developed in this work for effective determination of malathion. The sensing system consists of negatively charged aptamer probes, and polycationic proteins, protamine, as well as exceptional colorimetric nanoprobes, barely gold nanoparticles (AuNPs). Protamine molecules bound to aptamer probes hinder the aggregation of AuNPs, while no such inhibition is maintained when aptamer-specific malathion is introduced into the solution, thus leading to the solution color change from red to blue observable by the naked eye. The assay is accomplished via a mix-and-measure step within 40 min with a detection limit as low as 1.48 µg/L (3σ/s rule). The assay method also exhibits high selectivity and good applicability for the quantification of malathion in tap water with recovery rates of 98.9%-109.4%. Additionally, the good detection accuracy is also confirmed by the high-performance liquid chromatography method. Therefore, the non-enzymatic, label- and device-free characteristics make it a robust tool for malathion assay in agricultural, environmental, and medical fields.